2015
DOI: 10.1090/proc/12909
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of stable processes with drift

Abstract: Suppose that d ≥ 1 and α ∈ (1, 2). Let Y be a rotationally symmetric α-stable process on R d and b a R d -valued measurable function on R d belonging to a certain Kato class of Y . WeThroughout this paper, unless otherwise stated, d ≥ 1 and α ∈ (1, 2). A rotationally symmetric α-stable process Y in R d is a Lévy process with characteristic function given by(1.1) The infinitesimal generator of Y is the fractional Laplacian ∆ α/2 := −(−∆) α/2 . Here we use ":=" to denote a definition. Denote by B(x, r) the open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…In that paper, they showed that, when µ(d x) = b(x)d x is absolutely continuous and belongs to the Kato class K d,α−1 , the martingale problem for L = ∆ α/2 + b · ∇ is well posed and the SDE d X t = d S t + b(X t )dt has a unique weak solution in the "classical" sense. As remarked in [10], our Theorem 1.4 does not cover these results in [10].…”
Section: Theorem 14 (A)mentioning
confidence: 73%
See 1 more Smart Citation
“…In that paper, they showed that, when µ(d x) = b(x)d x is absolutely continuous and belongs to the Kato class K d,α−1 , the martingale problem for L = ∆ α/2 + b · ∇ is well posed and the SDE d X t = d S t + b(X t )dt has a unique weak solution in the "classical" sense. As remarked in [10], our Theorem 1.4 does not cover these results in [10].…”
Section: Theorem 14 (A)mentioning
confidence: 73%
“…Some details of the proof of the uniqueness are spelled in the Appendix. After we have finished the first version of this paper, we were informed that very recently in [10] Chen and Wang studied on a related topic. In that paper, they showed that, when µ(d x) = b(x)d x is absolutely continuous and belongs to the Kato class K d,α−1 , the martingale problem for L = ∆ α/2 + b · ∇ is well posed and the SDE d X t = d S t + b(X t )dt has a unique weak solution in the "classical" sense.…”
Section: Theorem 14 (A)mentioning
confidence: 99%
“…For results on the well-posedness of the martingale problems for L b t , we refer the reader to [1,7,8] and the references therein. We remark here that if…”
Section: Remark 14mentioning
confidence: 99%
“…Therefore, we expect to obtain a similar expression of S λ like the identity (4). However, we first have to identify the class of drifts for which the term b(t, ·) · ∇ is "small enough" compared to ∂/∂t + △/2 and the perturbation argument works.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Chen and Wang [4] studied rotationally symmetric α-stable process with a drift belonging to the Kato class K d,α−1 (see [4, Definition 1.1]); they proved the existence and uniqueness, in the weak sense, of such a process and established sharp two-sided estimates for its heat kernel. Sharp two-sided Dirichlet heat kernel estimates for such a drifted α-stable process were derived in [3].…”
Section: Introductionmentioning
confidence: 99%